Impact of climate change on coffee production in Veracruz under a Ricardian approach - Guerrero Carrera, Jesús; Hernández Flores, José Alvaro (Ecosistemas y Recursos Agropecuarios, 2024)
The phenomenon of climate change has generated significant adverse consequences on coffee productivity and the income of producers around the world. The present study aims to evaluate the potential repercussions of climate change on coffee production in the Las Montañas region, Veracruz. To carry out this analysis, socioeconomic and environmental data were collected during the years 2022 and 2023, through a survey applied to a sample of 91 production units specialized in coffee cultivation. These data were subjected to ordinary least squares analysis, using the Ricardian approach. The results obtained indicate that the climate change will have a significant impact on the value of the land and that these effects will be differentiated between the different strata of producers, particularly affecting the smaller scale ones. The heterogeneity in climate sensitivity highlights the importance of considering specific strategies for different types of producers in order to reduce their dependence on coffee cultivation and reduce their vulnerability to the increasingly evident impacts of climate change.
Keywords: Land value, income, vulnerability, climatic variables, adaptation